The Facilitators’ Team Learning Behaviour in Enabling Women Spiritual Empowerment - Adi Suryani; Moh. Saifulloh; Kartika Nuswantara; Wahyuddin Wahyuddin; Siti Zahrok; Zainul Muhibbin; Soedarso Soedarso (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACT Preparation of the facilitating team is necessary for the facilitation and delivery of community empowerment programs. The facilitating team is required to not only plan the event but also to prepare the team's expertise and program materials. This motivates the facilitating team to participate in team learning since the knowledge and delivery skills of the facilitating team may be necessary for the empowerment process to be successful. The study focuses on observing the learning behaviour of the facilitating team. The study intends to investigate the facilitating team learning behaviors and enabling elements that affect the team learning process as they get ready to lead a program for spiritual empowerment for a women's community organization. The study adopts qualitative research design. The data are gathered through direct observation of the team's online interactions, community empowerment program, and learning workshops. The data are analyzed by using thematic analysis method. The study reveals that the facilitating team exhibits adaptable, collaborative, engaging, and participatory learning behaviors. These behaviors are influenced by three main aspects: the organizational system, team leadership and individual dimension. The study also reveals that the dynamic interaction of a team's social, psychological, and shared cognition influences the team's learning behavior. Furthermore, it shows that team learning behavior study requires considering both the social and individual dimensions of the members of the group.Keywords: team learning, women empowerment, learning behavior, organizational system, team leadershipTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersianÂ // Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//